Efficiency Strategy for Procurement of Raw Materials for Side Beam for Bogie with Material Requirement Planning at PT XYZ - Abdullah, Rosyid; Suseno (Jurnal Sistem Teknik Industri, 2024)
Companies in Indonesia must find the right solution in order to survive and compete in the era of globalization. Price competition is an important strategy in the competition between similar companies. Based on this, there is a need for a good understanding in the company regarding strategic financing planning in order to achieve predetermined goals efficiently. This efficiency can be characterized by minimal cost expenditure in order to obtain maximum profit. One way to get maximum profit is by implementing good inventory management PT XYZ is a train manufacturing company in Southeast Asia. The company produces various types of trains. There is a production planning for the Train XYZ project with a total production of 526 units of train components for the Side Beam for Bogie. Procurement of these raw materials, PT XYZ uses Lot for Lot (LFL) at a cost of Rp1,411,402. The use of the LFL system still has shortcomings, namely problems due to late delivery and inefficient procurement in terms of financing. The results of production planning research with several MRP methods that have been compared, it is concluded that POQ lot sizing is the most efficient procurement of raw materials other than LFL. In detail, the total cost with the POQ method amounted to Rp1,243,140 and decreased by 11.9%. The cost consists of procurement costs of Rp781,162 and storage costs of Rp461,978.